2015
DOI: 10.21863/johb/2015.4.2and3.013
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Job Burnout among Teachers in Private Professional Institutions

Abstract: Based on the results of the burnout questionnaire surveyed among 146 young teachers from private higher education institutions in Shanghai, this study presented an investigation of the actual situation of job burnout and explored the general influential factors of job burnout. In addition, self-development counseling was used as an intervention method for 46 selected participants who displayed warning signs of burnout. The results showed that: (1) The job burnout rate of young male teachers was significantly h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Finally, the result of this study is parallel to the study of Khan (2012) which revealed in his data analysis a low level of burnout among the full-time faculty at Fullerton College. While the finding of this study was found to support previous studies, the result is however opposite to what Sachdeva and Narwal (2015), had found out. The results of their study confirmed that teachers working in private professional institutions reported high level of burnout.…”
Section: Resultscontrasting
confidence: 99%
“…Finally, the result of this study is parallel to the study of Khan (2012) which revealed in his data analysis a low level of burnout among the full-time faculty at Fullerton College. While the finding of this study was found to support previous studies, the result is however opposite to what Sachdeva and Narwal (2015), had found out. The results of their study confirmed that teachers working in private professional institutions reported high level of burnout.…”
Section: Resultscontrasting
confidence: 99%
“…The item with the highest factor loading on this dimension is one referring directly to burnout, 'I feel burned out from my work. The Maslach Burnout Inventory has been employed in a number of studies among teachers across a range of cultural contexts, including Australia (Goddard, O'Brien, & Goddard, 2006;McCormick & Barnett, 2011), Brazil (Santana, De Marchi, Junior, Girondoli, & Chiappeta, 2012), China (Yu, Wang, Zhai, Dai, & Yang, 2015), Georgia (Bitsadze & Japaridze, 2016), Greece (Koustelios, 2001), India (Sachdeva & Narwal, 2015), Iran (Pishghadan & Sahebjam, 2012), Japan (Yatsunami & Arai, 2001), Latvia (Zakrizevska, 2015), The Netherlands (Schaufeli, Daaman, & Meirlo, 1994), Norway (Skaalvik & Skaalvik, 2014), South Africa (Nthebe, Barkhuizen, & Schutte, 2016), Spain (Guerrero, Gomez, & Moreno, 2011), Turkey (Ertürk & Keçecıoğlu, 2012), United Kingdom (Covell, McNeil, & Howe, 2009;Moneta, 2011) and United States of America (Abel & Sewell, 1999;Jennett, Harris, & Mesibov, 2003).…”
Section: Work-related Psychological Healthmentioning
confidence: 99%